Innovative Knowledge Management Collaboration Through Internet of Things - Abdullah, Embong; Muhammad Wasif, Nabeel (Penerbit UMP, 2015)
Nowadays communication is an essential part of our lives and Internet is one of the best medium to connect not only humans but other things such as services, systems and devices. A new paradigm shift has occurred in technology and the future is very near when every object will have its own identification and they can be connected just like humans. The implementation of this idea is also under process and few of its examples are already seen in the market such as Smart Thermostat, Smart washer/dryer. This is known as The Internet of Things or IOT, and this is the trend and where the future is. The basic idea behind this innovation is to make objects act like human. Radio Frequency Identification techniques (RFID) and related identification technologies will be used to tag the objects in the IoT. Many IoT devices have sensors that can register changes in temperature, light, pressure, sound, and motion. The IOT devices and system are integrated with internet using cellular, WIFI, 3G module, Wimax and each device is assigned a unique IP address which uses IPv6 address space. The benefit of these devices is that they work under low power and low bandwidth which make them special innovation. This paper describes the structure of IOT and its usage through library example. The starting section gives brief overview. Then it discusses the main architecture and trends of IOT. Finally a model for management of library with reference of IOT. Keywords: Internet of things; Sensors; RFID